Cosmological Dimensions in The Teachings of The Naqshabandi Sufi Order - Burhanuddin, Nunu; Syihab, Usman (KALAM, 2019)
In general, studies about tariqa have put more emphasis on aspects related to ritual teachings and spiritual experience of the Sufi leaders. Little has been studied so far about how teachings of a Sufi order are related to cosmological concepts. This paper aims to analyze the cosmological concepts that are taught in the teachings of the Naqshbandi Sufi order in the district of Pauh, the city of Padang, West Sumatera. Data for this research are gathered through interviews, observation and documentation. These data are then analyzed with content analysis method. The research find that the Naqshbandi order perceives the notion of sharia as one that is intimately related with divine revelation and the universe’s law of order, a holistic approach that regards deeds of a sālik (a Sufi traveler) as part of the cosmic order. The existing seven types of sharia law outline seven layers of heaven and earth. Thus, a mystic attainment of martabah hakikat (degree of reality) represents seven layers of heaven and earth, which are manifested through amaliah lathāif (inner ‘worship’ rituals) - all of which are attributed to internal parts of the human soul, such as brain, heart, spleen, liver, lungs and all internal parts of the human physical body. Within the Naqshbandi Sufi order, all sālik aredevised to be able to attain close relationship with God, and to become an imagery of human’s mystical potentials in their everyday lives’ activities.